The Italian Covid-19 Phase 2 in Piacenza: results of the first semester of 2020 and future prospective of new orthopedics surgical procedures - Maniscalco, Pietro; Quattrini, Fabrizio; Ciatti, Corrado; Gattoni, Serena; Puma Pagliarello, Calogero; Burgio, Valeria; Di Stefano, Giovanni; Cauteruccio, Michele; Giovanelli, Matteo; Magro, Alessandra; Capelli, Patrizio (Acta Biomedica Atenei Parmensis, 2020)
Introduction:During the pandemic, Piacenza’s Orthopedic and Traumatology Dep. firstly dealt with the emergency with the complete closure of all the elective surgical and outpatient activities.As general population, also healthcare workers were affected by Coronavirus, increasing difficulties of epidemic management.The aim of our study is to evaluate the activity trend of the first 6months of 2020 in our hospital.Data will be compared to the two semesters of 2019, in order to have two objective samples.Materials and Methods:We retrospectively analyzed all the orthopedics surgical procedures performed at Guglielmo da Saliceto Hospital (Piacenza, Emilia Romagna, Northern Italy)between 1/1/20 and 30/06/20. 2019 semesters (1/01/20-30/6/20 and 1/07/20-31/12/20) have been used as control group to evaluate the activity trend of the first six months of 2020, compared to the two semesters of 2019.Results:We noticed a significant increase of domestic and retirement houses accidents, a consistent increase in one-month mortality rate of 2020 first semester and a decrease of mean hospitalization time.About surgical procedures, we detect a drop in the total number: in the first semester of 2020 we performed 499 (-39.9%) surgeries less than the first semester of 2019 and 337 (-30.9%) then the second one. Traumatology recorded a decrease of 27.6% than the first semester of 2019 (-204 surgeries) and of 26.3% than the second one (-191 surgeries).Concerning orthopedic procedures, in comparison to the first semester of 2019 we registered a reduction of 57.6% (-295 surgeries) and of 40.2% to the second semester (-146 surgeries).Discussion and conclusion:Covid-19 forced a reorganization of the Italian Health System that led to a clear reduction of surgical procedures performed in the orthopedic and traumatology department.The “Phase 2” can’t be consider the last step of the emergency.We surely will have to get used to live with this enemy, at least until we will find an effective cure or a vaccine.